“Well, besides the fact that deployment kinda stinks…”: adolescent voices in literacy during military deployment - Sherbert, Vicki Luthi (Kansas State University, 2011)
By the end of March 2011, 2.3 million active-duty military personnel and reservists had deployed to combat operations in Iraq and Afghanistan (Golding, 2011). Many of them had experienced multiple deployments in which they served in war zones for 12 to 15 months, returned to the US for 12 months, and then deployed again to another war zone (Huebner & Mancini, 2008; Morse, 2006). Adolescents in military families whose service members are deployed repeatedly, and for longer durations, experience circumstances unique to current conflicts. Documents such as the Educator’s Guide to the Military Child During Deployment (retrieved 2008) recommend various literacy practices as a means of coping with the circumstances of deployment. This qualitative phenomenological inquiry seeks to extend the body of research in the area of adolescent literacy by examining the perceptions of adolescents regarding their out-of-school literacy practices within the experience of deployment. In this study, the perspectives of five adolescents were examined regarding their literacy practices as they shaped their identities, enacted agency, and navigated structures of power during deployment. Phenomenological analysis, critical discourse analysis, and sociocultural theory were applied to data gathered from initial interviews, literacy logs, and follow-up interviews. During the phenomenological analysis, descriptions of each participant’s experiences were developed, replete with the words and expressions of the adolescents themselves. Horizontalization of significant statements from these descriptions yielded a composite description offering an understanding of what it is like to engage in out-of-school literacy practices within the circumstances of military deployment. Three themes emerged; ambiguity, responses, and roles. A theoretical analysis utilizing critical discourse analysis and sociocultural theory examined the discourses of the participants and interpreted relationships between the adolescents’ literacy practices and their experiences with deployment. This examination offered insight to the ways these adolescents established identity and enacted agency within power circulations as their families experienced deployment. This study places the voices of adolescents at the foreground of consideration. Listening to their words and reading their texts offers true insight into their literacy practices as they navigate the lived experience of deployment.
Keywords: Adolescent literacy; Family literacy; Military deployment; Education, General (0515)